Integrate Reengineering and TQM: An Attempt to Redefine Reformation - Ciptono, Wakhid Slamet (UI Scholars Hub, 2007)
This study examines the structural relationships between TQM, Reengineering, Operational Excellence in downstream and upstream sectors, Reformation, and sustainable community development program. A good understanding of how oil and gas industry should integrate mainstreaming the approach to sustainable community development into policymaking. Sustainable community development should be implemented by considering the links between change management through TQM and reengineering, operational excellence applications, and the real reformation. Recognizing that contributions of reformation (via the amendment of law of the Republic of Indonesia No. 22/2001 concerning oil and natural gas) in the sustainable community development is a key component in the Indonesia’s economy reform and recovery. Empirical evidences find that seven causal paths specified in the hypothesized model were found to be positive and statistically significant. Furthermore empirical results suggest that reengineering has a positive and significant indirect effect on sustainable community development program through its direct effect on operational excellence in supply chain; and reformation. The result also shows that a complete model fit and the acceptable parameter level which indicate the overall parameter are good fit between the hypothesized model and the observed data. By concentrating on a single industry (oil and gas) is that SEM specification of the structural relationship model between six constructs can be more complete and specific because unique characteristics of the oil and gas industry can be included (upstream and downstream chain activities). Finally, the particular design of the research and the findings suggest that the structural model of the study has a great potential for replication to business as well as public sectors.